Facade standardization on heritage building in tourism city: Singapore, Penang Island, and Cameron Highland / Mohd Zukhairi Osman - Osman, Mohd Zukhairi (2002)
Years 1998 till 2002 were the speculation era in the millennium that brought down he world economic cause existing and emanating the speculator, which incited the world’s investor. In this world of he recession, Malaysian government had tried many things to increasing the economic to he save level. And now the united state incited the world residents about the terrorist, which Islamic country had involved too. That’s another reasons why the Malaysia economic drops. While correcting the reduce of Malaysia economic, Dato’ Seri Dr. Mahathir Mohammad, Malaysian Prime Minister had gave his idea to the OIC (Organisation of Islamic Congress) on how to manage the recession clear the mess in Islamic Country from the terrorist. He had suggested investing to the tourism interest on he Islamic Country. In other words, the Islands, villages, and cities could attract the tourist. This dissertation is concentrate on how the facade standardization and heritage building conservation had been done and can attracts peoples and tourist to visit them. The writer had been chose the Cameron Highland, Penang Island, and Singapore as his case study. Many heritage building emanate in this country and should be realized by the Authority on he building conservation and fagade standardization. Conservation is not new in our country, but they need a concentration, understanding, conscientious, and passions. The term of conservation are includes; preservation, alteration, reconstruction and other thing that should be notified. This is importance in achieving the levels of conservation. Needs to maintain the originality including the memory lane of the heritage building, and the cultural significant will make a big benefit. There are several issues could be raised, such as; why the heritage building conservation is importance? And do the fagade standardization could be an attracting to the tourist? In he end of this dissertation, the writer will make conclude and suggestion on what could be done. Can the heritage building conservation achieve to its recommended levels and how the fagade standardization can be related to the environment such o colour, materials and other things?